Proximity Relationships in Rhodopsin - Wu, Cheng-Wen (1972)
Energy transfer was used as a spectroscopic ruler to deduce proximity relationships within bovine rhodopsin in digitonin solution. Rhodopsin was specifically labeled with fluorescent chromophores at three sites. Site A was alkylated by fluorescent derivatives of iodoacetamide. Site B was labeled by fluorescent disulfides, by a disulfide-sulfhydryl interchange reaction. Sites A and B are sulfhydryl residues. Acridine derivatives were tightly bound to site C by noncovalent interactions. The labeled rhodopsins retained their 500-nm absorption band and were regenerable after bleaching, suggesting that the fluorescent probes did not grossly perturb the conformation of the protein. A fluorescent chromophore at one of these sites served as the energy donor, while 11-cis retinal was the energy acceptor. The efficiency of singlet-singlet energy transfer was determined from the quantum yield and excited-state lifetime of the donor in the presence and absence of the acceptor. By Förster's theory, the apparent distances between 11-cis retinal and sites A, B, and C were calculated to be 75,55, and 48 Å, respectively. Energy transfer measurements on rhodopsin labeled at two of these sites gave these apparent distances: 35 Å for A to B, 32 Å for A to C, and 30 Å for B to C. These energy transfer studies suggest that the rhodopsin molecule has a length of at least 75 Å. Thus, the rhodopsin molecule appears to be sufficiently long to traverse the disc membrane. Rhodopsin might act as a light-controlled gate.